Shape memory composites for comfort fitting - Azharuddin Mohamed Naseem (Nanyang Technological University, 2021)
Shape memory polymer has the potential to be used in various industries. Its properties can be applied for comfort fitting purposes such as shoe insoles. Comfort fitting for shoe insole purpose requires the polymer to be functional at body temperature of a human being (37°C). This report aims to develop an SMP to be used as comfort fitting option. The SMP need to have the ability to hold its shape (programmable) when stretched and provide the necessary comfort to its users. This material has the ability to be programmed at body temperature which adds to the comfortability factor. This report studies the elastic and shape memory properties of this material and its potential usage in developing new shape memory that are not only stretchable but also programmable for comfort fitting. Another important factor while developing this new kind of insole, the insole has to be lightweight. Finally, this report discusses the future prospects for the advancement of wearable technology using such programmable material.